Towards ternary optical communication by soft decoding - Mokhtar, Makhfudzah; Abdullah, Mohamad Khazani; Walker, Stuart D. (IEEE, 2006)
Unlike the conventional 2M level soft decision, a new soft decoding technique is proposed on optical ternary system. It is shown that (852,742,6) code improves at 10 dB coding gain whilst increasing the code efficiency.